DAYA TAHAN PENDIDIKAN LANGGAR DI TENGAH ARUS MODERNISASI PENDIDIKAN ISLAM - Syamsudini (Al'Adalah, 2016)
Islam has come in Indonesia for about 14 Century. Indonesian people have believed on Islam for long period. The number of Muslim in Indonesia shows the spread of Islam in this country is more success than in other countries which has similar process. The spread of Islam in Indonesia cannot be separated from the role and ability of mubaligh in conveys the Islam messages. Especially in education path, the mubaligh utilizes amount of education institute as a media for spreading Islam. One of the media is Langgar that is become as Islamic centre learning especially in learning the primary source of Islam that is Alquran. Education in Langgar is one of the social institutions that cannot escape from the change. Yet, the change happens slowly and on small scale, that is in aspect learning strategy. The factors which causes the change is by finding the new paradigm about the learners, from teacher oriented to student oriented. It is demonstrated by publishing several books which told about “how to learn fast” and so on. The new findings inspire the experts of Islamic education to arrange the guidelines of how to learn Alquran – based active student – which is adopted by several institutions of Langgar education.